Inovasi Pembelajaran Sistem Rem Cakram Menggunakan Media Audio Visual untuk Meningkatkan Minat Belajar Siswa SMK - Aci Primartadi; Diki Ariyanto; Arif Susanto (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine: (1) the application of audio video learning media for disc brake systems can increase students' interest in learning the subject of motorcycle disc brake systems in class XI of SMK Ma'arif Nu 1 Bener Purworejo. (2) increasing students' interest in learning after the application of audio video learning media for motorcycle disc brake systems in class XI of SMK Ma'arif Nu 1 Bener Purworejo. The research method used in this study is the research design using Classroom Action Research (Research with action). The subjects of this study were students of class XI TSM SMK Ma'arif NU 1 Bener in the 2024-2025 academic year consisting of 31 students. The data collection techniques used were Documentation of evidence of learning implementation and Questionnaires (Questions). The technique used to analyze the data in this study was a quantitative technique. Based on the results of the study, it can be seen that during the classroom action research, there was a significant increase in each cycle, previously in the pre-cycle stage, students' interest in learning only reached 60% and increased to 70.97% in cycle I, an average of 75.42 was obtained and entered the category